Strategic Use of Direct and Online Marketing to Enhance Customer Retention - Rahmawati, Reni; Sulastri, Lilis (Islamicate Institute, 2022)
This study explores how the integration of direct and online marketing can improve customer retention in increasingly competitive and digitalized markets. Grounded in relationship marketing and CRM theory, it analyzes the roles of personalized communication, digital engagement, and multichannel strategy in fostering loyalty. Using qualitative thematic analysis of verified academic and institutional sources, the research finds that direct marketing enhances trust and emotional connection, while online marketing offers scalable, interactive engagement. When harmonized through CRM tools and lifecycle planning, these approaches create cohesive experiences that reinforce customer satisfaction and loyalty. The study also addresses ethical considerations, cultural factors, and emerging market contexts—offering a nuanced framework for retention strategy. The findings contribute to marketing theory by integrating formerly distinct approaches and provide actionable insights for practitioners. By aligning strategic communication across platforms, businesses can deepen brand relationships and ensure sustainable customer value.